INCIDENCE OF POLYPHARMACY AND DRUG RELATED PROBLEMS AMONG ELDERLY IN TERTIARY CARE HOSPITAL – A DESCRIPTIVE STUDY - SHARON, TABITHA; VEMPARALA, CHAITHRA; Kandukuri, Sri Vasavi; Komati, Madhuri; Gottapu, Bhargavi (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Drug-related problems are most common in Geriatrics. The increasing number of available drugs and drug users as well as more drug regimens led to many drug related problems which increases the health-care cost, mortality, morbidity, and also decreases the quality of life. The main objective of this study is to assess the incidence of polypharmacy and drug-related problems among elderly admitted in tertiary care hospital. Methods: The study was conducted in a tertiary care hospital after obtaining ethical clearance from the Institutional Ethical Committee. The medication information along with medical data and patient demographics such as name of the patient, age, sex, chief complaints, laboratory data, diagnosis along with therapeutic data such as name of the prescribed drugs, dose, dosage, frequency, route of administration, duration of treatment, and any new or existing drug-related problems were noted in a case collection form by bed-side counseling, case sheets, laboratory reports and were documented. The drug-related problems (DRPs) were categorized using Pharmaceutical Care Network Europe classification v 9.0 classification. Statistical analysis was done using Chi-square test. Results: of 151 Participants considered for the study 97 (64.24%) were males and 54 (35.76%) were females. The incidence rate of DRPs was found to be 86.09% and 1.45 DRPs per patient. In a total number of sample population, patients with DRPs were 120 and without DRPs were 21. Conclusion: DRPs mostly observed in geriatric population as they receive multiple medications for multiple disease conditions and active role of clinical pharmacist is necessary to identify and resolve them. DRPs identified must be accepted by the physicians and cooperation of patients and physician is necessary to resolve DRPs. Further studies are required to prove that the polypharmacy plays a major role in developing DRPs.